Effect of a superconducting defect on the Cooper pairs of a mesoscopic sample (2014)
We investigate the vortex state in a very long prism of square cross section with a central square defect in the presence of an external perpendicular magnetic field. We considered that the inner defect edge is in contact with a thin superconducting layer at higher critical temperature and/or with a dielectric material, while the outer edge of the sample is in contact with the vacuum. We have evaluated the superconducting order parameter, magnetization and vorticity as a function of the size of the defect at the first vortex penetration field. Therefore we conclude and we are able to show that circular geometry of the vortices near to the defect is mildly modified by the enhanced superconductivity at the edge of the hole. © The authors; licensee Universidad Nacional de Colombia.